The preimplantation genetic testing clinical outcomes of biopsy on vitrification‐warming embryos: A retrospective study. Issue 7 (18th May 2022) - Ding, Min; Diao, Zhenyu; Zhou, Jianjun
Abstract: Aim: The objective of this study was to assess whether PGT conducted with previously untested vitrified embryos affect the clinical outcomes. Methods: A total of 49 patients who underwent biopsy on vitrification‐warming embryos for PGT were enrolled from January 2016 to January 2019. The cleavage‐stage embryos were thawed and cultured into the blastocyst stage for biopsy. During this period, 195 patients underwent routine PGT and FET, whose embryos were biopsied before frozen were used as the control group. The clinical outcomes were further compared between the two groups after a 1:2 PSM. Results: There were 47 transferable blastocysts in 30 patients, while 19 patients without transferable embryos, who performed biopsy on vitrification‐warming embryos for PGT. During this study period, 27 patients have already underwent FET with the clinical pregnancy rate was 66.7% (18/27). After 1:2 PSM, 24 patients in the biopsy on vitrification‐warming embryo group and 48 patients in the control group were compared, the clinical pregnancy rate (68.8% vs. 70.8%, p = 0.86), miscarriage rate (18.2% vs. 11.8%, p = 0.86), or live birth rate (52.1% vs. 62.5%, p = 0.40) had no significant difference. And the transferable blastocyst rate or the clinical pregnancy rate in the vitrification‐warming cleavage‐stage embryo group was not significantly different from those in the vitrification‐warming blastocyst group. In addition, the PGT clinical outcomes of biopsy on vitrification‐warming embryos had no significant difference between IVF‐fertilized embryos and ICSI‐fertilized embryos. Conclusion: Biopsy on the vitrification‐warming embryos with a dual vitrified cryopreservation does not affect the embryo quality or the PGT clinical outcomes.